Numerical simulation for entropy generation in peristaltic flow with single and multi-wall carbon nanotubes - Ijaz Khan, Muhammad; Farooq, Shahid; Hayat, Tasawar; Shah, Faisal; Alsaedi, Ahmed (International journal of numerical methods for heat & fluid flow, 2019)
Purpose The novel mechanical, chemical and thermodynamics characteristics of both single- and multi-wall carbon nanotubes (CNTs) make them a subject of much attention for the scientists and engineers from all domains. Fluid flows subject to CNTs are significant in biomedical engineering, energy storage systems, domestic and industrial cooling, automobile industries and solar energy collectors, etc. Keeping such effectiveness of CNTs in mind, this paper aims to examine peristaltic flow subject to CNTs in an asymmetric tapered channel. Both single and multiple walls CNTs are considered. The viscosity of nanomaterial depends on nanoparticles volume fraction and temperature. Total entropy rate through second law of thermodynamics is calculated. Heat source/sink and nonlinear heat flux are accounted. Design/methodology/approach The complicated flow expressions are simplified through lubrication approach. The velocity, temperature and entropy expressions are numerically solved by the built-in-shooting method. Findings The solutions for entropy generation, temperature and velocity are plotted, and the influences of pertinent variables are examined. The authors noticed that entropy generation is an increasing function of the Brinkman number. Originality/value The originality of this work is to communicate peristaltic CNTs-based nanomaterial peristaltic flow of viscous fluid in an asymmetric channel. No such consideration is yet published in the literature.